Comparison of polyolefin biocomposites prepared with waste cardboard, microcrystalline cellulose, and cellulose nanocrystals via solid-state shear pulverization. (28th September 2015) - Iyer, Krishnan A.; Flores, Amanda M.; Torkelson, John M.
Abstract: As a significant part of municipal solid waste (MSW), waste cardboard (CB) is a sustainable, inexpensive, and rich source of cellulose. Previous studies of polyolefin/CB composites have reported modest enhancement to major reduction in modulus and major reduction in elongation at break values relative to neat polymer. Here, green hybrids of low density polyethylene (LDPE) and polypropylene (PP) with 5–25 wt% CB are made by solid-state shear pulverization (SSSP), which achieves both size reduction of 2–3 cm sized CB pieces to the micron level and dispersion in polymer. The properties obtained with CB incorporation in LDPE and PP are compared and contrasted with those obtained with incorporation of microcrystalline cellulose (MCC) and cellulose nanocrystal (CNC). Polyolefin composites with CB made by SSSP exhibit major enhancement in Young's modulus (63% and 71% increases for 10 wt% CB in LDPE and 15 wt% CB in PP, respectively). The PP/CB composites exhibit a broad range of property enhancements relative to neat PP, including a nearly 50% nucleating efficiency, as much as an 8% increase in PP crystallinity, and a factor of ∼3 decrease in crystallization half-time. Well-dispersed CB particles improve LDPE and PP thermo-oxidative stability as shown by thermogravimetric analysis (∼5–20 °C increase in 20% mass loss temperature in air with 15–20 wt% CB addition) and isothermal shear flow rheology. Similarly, post-SSSP high-temperature, long-time melt mixing results in no apparent degradation of LDPE/CB and MCC composites whereas LDPE/CNC composites show major degradation. When incorporated into polyolefin composites, low cost, cellulose-rich MSW can often produce reinforcement similar to glass fibers and thus has potential as filler for structural composite applications. Graphical abstract: Highlights: Well-dispersed polyolefin hybrids are made with waste cardboard, MCC and CNC. Effective size reduction of 2–3 cm CB pieces to micron scale and dispersion were achieved. 63 and 71% increases in modulus for 10 wt% CB in LDPE and 15 wt% CB in PP. Composites show a 50% nucleating efficiency and 5–20 °C increase in thermal stability. Low cost, cellulose-rich waste cardboard provides reinforcement similar to glass fibers.